Fruit Properties of Promising Rose Hips (Rosa spp.) from the North-eastern Anatolia Region of Turkey - Ercisli, Sezai; Guleryuz, Muharrem (Asian Journal of Chemistry, 2010)
This study was conducted to select promising Rose hip (Rosa spp.) phenotypes in an area situated in North eastern Anatolia of Turkey from 1993 to 1995. The native rose hip populations consisted of approximately 2500 seedling shrubs and were examined with regard to shrub and fruit properties. Among phenotypes, nine of these, three Rosa dumalis, two Rosa canina and one Rosa hirtissima, Rosa pisiformis, Rosa villosa and Rosa montana found to be superior were selected and evaluated for fruit characteristics. Promising selections exhibited a range of 3.01–5.49 g fruit weight, 61.67–74.20% fruit flesh ratio, 29.02–37.09% total soluble solid and 348–911 mg/100 g ascorbic acid, respectively. These results suggest that the rose hips selected may be suitable for commercial cultivation in the region.